Neuroprotection in Hypoxic-Ischemic Brain Injury Targeting Glial Cells - Mucci, Sofia; Ines Herrera, Maria; E. Barreto, George; Kolliker-Frers, Rodolfo; Capani, Francisco (Current Pharmaceutical Design, 2017)
Brain injury constitutes a disabling health condition of several etiologies. One of the major causes of brain injury is hypoxia-ischemia. Until recently, pharmacological treatments were solely focused on neurons. In the last decades, glial cells started to be considered as alternative targets for neuroprotection. Novel treatments for hypoxia-ischemia intend to modulate reactive forms of glial cells, and/or potentiate their recovery response. In this review, we summarize these neuroprotective strategies in hypoxia-ischemia and discuss their mechanisms of action.
Keywords: pharmacological treatments